Cooperative recruitment of Yan via a high-affinity ETS supersite organizes repression to confer specificity and robustness to cardiac cell fate specification. - Boisclair Lachance, J.F.; Webber, J.L.; Hong, L.; Dinner, A.R.; Rebay, I. (Genes & Development, 2018)
Cis-regulatory modules (CRMs) are defined by unique combinations of transcription factor-binding sites. Emerging evidence suggests that the number, affinity, and organization of sites play important roles in regulating enhancer output and, ultimately, gene expression. Here, we investigate how the cis-regulatory logic of a tissue-specific CRM responsible for even-skipped (eve) induction during cardiogenesis organizes the competing inputs of two E-twenty-six (ETS) members: the activator Pointed (Pnt) and the repressor Yan. Using a combination of reporter gene assays and CRISPR-Cas9 gene editing, we suggest that Yan and Pnt have distinct syntax preferences. Not only does Yan prefer high-affinity sites, but an overlapping pair of such sites is necessary and sufficient for Yan to tune Eve expression levels in newly specified cardioblasts and block ectopic Eve induction and cell fate specification in surrounding progenitors. Mechanistically, the efficient Yan recruitment promoted by this high-affinity ETS supersite not only biases Yan-Pnt competition at the specific CRM but also organizes Yan-repressive complexes in three dimensions across the eve locus. Taken together, our results uncover a novel mechanism by which differential interpretation of CRM syntax by a competing repressor-activator pair can confer both specificity and robustness to developmental transitions.